Improving Students’ Reading Comprehension by Using Sq3r Strategy at Seventh Grade of SMPN 1 Pekutatan - Primandana, I Made Hari (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aims to improve students' reading comprehension of descriptive text through SQ3R strategy for students of class VII E SMP N 1 Pekutatan. The subjects of this study were students of class VII E SMP N 1 Pekutatan which amounted to 24 students. The researcher used Classroom Action Research (CAR) as a research method to identify and solve problems in students' reading comprehension. This study went through 2 cycles consisting of four stages, namely planning, implementation, observation and reflection. To collect data, researchers obtained information from observations and tests conducted. The result of this study is that there is an increase in students' reading comprehension by using the SQ3R strategy. Besides, observation shows an increase in the number of students who were active and enthusiastic in learning reading comprehension of descriptive text. The test results showed that 7 or 29.17% of students passed the minimum score criteria in the pre-test, 11 or 45.83% of students passed the minimum score criteria in cycle I, and 19 or 79.17% of students passed the minimum score criteria in cycle II. It can be concluded that there is a significant improvement of students' reading comprehension on descriptive text using SQ3R strategy